Sensitivity of inland water bodies, natural vegetation and agriculture to weather extremes and to climate change - Mika, János; Farkas, Andrea (JOURNAL OF LANDSCAPE ECOLOGY, 2017)
The aim of this paper is to comprehend possible impacts of the atmospheric extreme events and of the expected climate change on three components of the landscape: hydrology and water management, natural vegetation, agriculture and food supply. These components are presented in the three columns of both matrices edited to comprehend the ecological impacts of weather extremes and climatic change. The 12 lines of the weather extremes include extreme cold day and night, extreme hot day and night, long heat wave, severe drought, heavy rainfall, long rain period, heavy snowfall and snow accumulation, evenly bright day, thunderstorm with lightning and hail, stormy wind including tornado, long lasting lack of wind, haze or fog, freezing rain and surface icing. Regional climate changes in Hungary, represented in the nine lines of the second matrix, include increased temperature in all seasons, less extreme cold days and nights, more extreme warm days and nights, longer heat waves in summer, less rainfall in the warm half-year, longer dry periods, more drought, more heavy or torrential rain, less snowy days, shorter snow cover, more sunshine in summer. These expert-based matrices are connected by a table of the IPCC that connects the weather extremes on one hand, and the recent and projected future trends concerning the extremes. The conclusion is that just a small part of all weather extremes exhibit trends and clear future changes. Hence, one should improve resilience to these extremes not because of climate change, but because they frequently occur even in the present climate.